Thermal Analysis of Claytan Porcelain with Potassium Feldspar Additions - Zulkifli, Mohd Azmi; Mohd, Norhayati (Tropical Scientific Journal, 2026)
Objective: The objective of this study is to investigate the thermal behavior of Claytan porcelain blended with varying weight percentages of potassium feldspar using Thermogravimetric Analysis (TGA) and Differential Thermal Analysis (DTA). The study aims to understand how different feldspar compositions influence thermal stability, sintering behavior, phase transformations, and overall material performance. Research Method: This experimental study analyzes Claytan porcelain mixed with different weight percentages of potassium feldspar. Thermogravimetric Analysis (TGA) was used to measure weight loss associated with thermal events, while Differential Thermal Analysis (DTA) was performed to identify endothermic and exothermic reactions during heating. Thermal changes, moisture evaporation, dehydroxylation, crystallization, and high-temperature phase transformations were evaluated to determine the influence of feldspar content on porcelain behavior. Findings: The TGA results show early weight loss below 59 °C due to moisture evaporation and a more significant mass loss around 412 °C linked to chemical interactions between porcelain and potassium feldspar. Total weight loss is low (0.44%–0.52%), indicating excellent thermal resistance across all formulations. DTA results reveal endothermic peaks at 56 °C (moisture removal), 510–515 °C (kaolinite dehydroxylation), and exothermic peaks at 967–981 °C (crystallization of kaolinite derivatives). Endothermic reactions above 1130 °C without weight loss suggest structural phase changes such as mullite and glassy phase formation. These results confirm stable thermal behavior and characteristic phase transitions essential for porcelain densification. Originality: This study offers new insights into how varying additions of potassium feldspar influence the thermal stability, phase transformation behavior, and sintering performance of Claytan porcelain. By combining TGA and DTA results, the research provides a deeper understanding of the role of feldspar as a fluxing agent, contributing valuable information for optimizing porcelain formulations in industrial ceramic manufacturing